Productive Economic Da’wah of KH. MA. Sahal Mahfudh - Ahmad Dalhar Muarif; Jamal Ma'mur Asmani; Muhammad Mulin Ni'am; Saib Abdillah (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
This study will discuss the thoughts and practices of M.A. Sahal Mahfudh's economic da'wah. Among the economic ideas of KH. MA. Sahal Mahfudh is to ground the sharia economy, the urgency of the market as a means of business transactions, encourage people to become productive, bank interest, allocate assets, and economic empowerment. This research is field research with a document study approach. Data collection methods using observation and interviews and technical data analysis using the Miles and Huberman technique. KH. MA. Sahal Mahfudh views that humans will achieve happiness in the world and the hereafter if they can unite the main human functions as ibadatulllah and immaratul ard. Thoughts and actions of proselytizing the productive economy of KH. MA. Sahal Mahfudh is, following maqashidus sharia, the objectives of implementing Islamic shari'ah, especially in the context of hifdhu al-mal (safeguarding property). Sufficiency and economic prosperity are the starting point for strengthening faith, developing the quality of education, and maturing the people's national insight. Hifdhu al-mal is the key to the success of other maqashidus sharia, namely protecting religion, soul, mind, and offspring.